ECONOMIC IMPACT OF EARTHQUAKES IN TURKEY - Musurmonqulov Asadbek Shavkatjon ugli (Journal of new century innovations, 2023)
Abstract: This article provides information about the earthquakes that occurred in Turkey and their impact on the economy.